Increased serum erythropoietin but not red cell production after 4 wk of intermittent hypobaric hypoxia (4000 - 5500m) - Gore, C. J.; Rodriguez, F. A.; Truijens, M. J.; Townsend, N. E.; Stray-Gundersen, J.; Levine, B. D. (Journal of Applied Physiology, 2006)
This study tested the hypothesis that athletes exposed to 4 wk of intermittent hypobaric hypoxia exposure (IHE 3h/d, 5d/wk at 4000-5500m) or double-blind placebo increase their red blood cell volume (RCV) and hemoglobin mass (Hbmass) secondary to an increase in erythropoietin (EPO). Twenty-three collegiate level athletes were measured before (PRE) and after (POST) the intervention for RCV via Evans blue (EB) dye, and in duplicate for Hbmass using CO-rebreathing. Hematological indices including EPO, soluble transferrin receptor (sTfr) and reticulocyte parameters were measured on 8-10 occasions spanning the intervention. The subjects were randomly divided among hypobaric hypoxia (HYPO n=11) and normoxic (NORM n=12) groups. Apart from doubling EPO concentration 3h after hypoxia there was no increase in any of the measures for either HYPO or NORM groups. The mean change in RCV from PRE to POST for the HYPO group was 2.3% (95% confidence limits = -4.8 to 9.5%) and for the NORM group was -0.2% (-5.7 to 5.3%). The corresponding changes in Hbmass were 1.0% (-1.3 to 3.3%) for HYPO and -0.3% (-2.6 to 3.1%) for NORM. There was good agreement between blood volume (BV) from EB and CO; BVEB = 1.03 BVCO + 142, r2=0.85, p<0.0001. Overall, evidence from four independent techniques (RCV, Hbmass, reticulocyte parameters and sTfr) suggests that IHE did not accelerate erythropoiesis despite the increase in serum EPO.